Residual Performance and Biomechanical Asymmetries During Jumping Tasks in Female Athletes at 9 Months After Anterior Cruciate Ligament Reconstruction. - Warnecke, Berit Flora; Richter, Chris; King, Enda; Paternoster, Florian Kurt (Orthopaedic Journal of Sports Medicine, 2024)
Background: Biomechanics and anterior cruciate ligament injury mechanisms differ in males and females. There is a need for more data on between-limb biomechanical differences after anterior cruciate ligament reconstruction (ACLR) in females. Purpose: To explore biomechanical asymmetries throughout the kinetic chain during the single-legged (SL) and double-legged (DL) countermovement jump (CMJ) and drop jump (DJ) in female athletes after ACLR. Study Design: Descriptive laboratory study. Methods: Kinematic and kinetic between-limb differences were analyzed during the SL and DL CMJ and DJ in 67 female athletes 9 months after ACLR. Biomechanical and performance asymmetries between limbs during the jumps and isokinetic strength testing were analyzed with statistical parametric mapping. The entire stance phase was used for the paired t tests of the biomechanical variables, with Cohen d effect sizes of significant portions of the stance phase (reported as % of stance) calculated in a point-by-point manner. Results: Decreased vertical ground-reaction force, internal knee abduction moment, knee internal rotation angle, hip external rotation angle, internal ankle eversion, and external rotation moments were seen in the ACLR limb during all 4 vertical jump tests. The greatest number and highest value of differences were found during the DLDJ, with asymmetries having medium to large effect sizes. They tended to appear more frequently in the concentric phase (50% to 100% of stance) during the SLCMJ and DLCMJ and in the eccentric (0% to 49% of stance) and concentric (50% to 100% of stance) phase during the SLDJ and DLDJ. For the SLCMJ, SLDJ, and quadriceps strength, performance asymmetries of >15% were detected but not for change of direction. Conclusion: The findings suggest that return-to-play testing in female athletes should examine the entire stance phase and include assessments of kinetic and kinematic variables throughout the kinetic chain. Greater deficits were highlighted in the DJ than in the CMJ, and greater performance asymmetries were evident in the SL tasks, with greater kinetic and kinematic and compensatory strategies evident in the DL tests. Clinical Relevance: Biomechanical analysis focusing on contralateral compensation strategies and sex-specific interventions are necessary before return to play.